2002
DOI: 10.1007/s00464-001-8341-1
|View full text |Cite
|
Sign up to set email alerts
|

After 10 years and 1903 inguinal hernias, what is the outcome for the laparoscopic repair?

Abstract: The laparoscopic approach is a safe form of inguinal hernia repair that offers the patient a shorter and less painful recovery with an extremely low recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 10 publications
2
25
0
4
Order By: Relevance
“…13,14 But the time taken to daily activities and to work was significantly less in the laparoscopy group, this argument seems to be of little worth. [15][16][17] There was no major complication observed in either group like any major vascular injury, visceral injury or bladder perforation only intraoperative inadvertent peritoneal breach was seen that difference was not significant between the two groups and the findings are consistent with the observations made by Ramshaw et al 18 In this study the postoperative pain following laparoscopic surgery was lower than that of open surgery at any given time and this difference was statistically significant p<0.05. This may be attributed to reduction in the size of incision, no need of extra or bilateral incisions in case of bilateral hernias, minimal dissection and less handling of cord structures.…”
Section: Discussionsupporting
confidence: 88%
“…13,14 But the time taken to daily activities and to work was significantly less in the laparoscopy group, this argument seems to be of little worth. [15][16][17] There was no major complication observed in either group like any major vascular injury, visceral injury or bladder perforation only intraoperative inadvertent peritoneal breach was seen that difference was not significant between the two groups and the findings are consistent with the observations made by Ramshaw et al 18 In this study the postoperative pain following laparoscopic surgery was lower than that of open surgery at any given time and this difference was statistically significant p<0.05. This may be attributed to reduction in the size of incision, no need of extra or bilateral incisions in case of bilateral hernias, minimal dissection and less handling of cord structures.…”
Section: Discussionsupporting
confidence: 88%
“…As with other mesh repairs, clinically relevant seromas occur after TEP at a frequency of about 1% to 6% [1,7,9,12,17,23,29]. If a postoperative ultrasonographic check is routinely performed, a correspondingly higher rate of fluid collections is found.…”
Section: Meshmentioning
confidence: 97%
“…The median operative times for the laparoscopic groups were significantly longer than the times for the control groups. In the hands of experienced laparoscopic surgeons beyond the learning curve, times for laparoscopic repairs are usually equal to or even faster than times reported for open repairs [34]. In randomized studies reporting this parameter, operative times are excessively long, telling us that the surgeons are early in their laparoscopic experience.…”
Section: How Far Have We Come?mentioning
confidence: 99%
“…Fortunately a small group of international and U.S. surgeons came to a different conclusion: If one could duplicate a Stoppa repair laparoscopically, one could duplicate the low recurrence rate achieved by a posterior mesh repair. They found that a wide laparoscopic dissection with complete coverage of the indirect, direct, and femoral spaces resulted in recurrence rates that were <1-2% for both primary and recurrent hernias [18,19,34]. Complication rates and operative times matched or in some cases bettered the open approach.…”
Section: How Far Have We Come?mentioning
confidence: 99%